Design and development of samarium cobalt based permanent magnet flow meter for 100 NB pipe in sodium circuits. (February 2015) - Rajan, K.K.; Sharma, Vijay; Vijayakumar, G.; Jayakumar, T.
Highlights: Design and testing of non invasive and passive SmCo based PMFM. SmCo PMFM has 55% lower weight than existing ALNICO-V PMFM. SmCo PMFM has 102% higher sensitivity than existing ALNICO-V PMFM. Design optimization and sensitivity estimation of SmCo PMFM with FEM analysis. Review of flow measurement techniques for Liquid sodium in large SS pipes. Abstract: Liquid sodium is used as coolant in sodium cooled fast reactors (SFR) due to its favorable nuclear properties and excellent heat transfer properties. Good electrical conductivity of sodium is effectively utilized for measurement of flow in primary and secondary circuits of the reactor. Alnico-V based permanent magnet flow meters (PMFM) are used to measure the flow of liquid sodium in stainless steel (SS) pipes of diameter ranging from 15 NB (Nominal Bore) to 800 NB. These PMFMs become bulky and heavy and are less sensitive for flow measurement in large pipes with diameter above 100 NB. To increase the sensitivity and reduce the weight, a new PMFM suitable for 100 NB pipe is designed and developed with SmCo magnet. The performance of SmCo based flow meter is evaluated experimentally in an existing sodium loop by varying sodium temperature and flow rate. Overall weight and sensitivity of the new design is compared with Alnico-V flow meters. Three dimensional Finite Element Modeling (FEM) is carried out to establish, modeling as an alternate method for calibration. In modeling and simulation, magnetic field distribution across the flow meter pipe and its effects on flow meter voltage signals are analyzed. The effect of sodium temperature on flow meter voltage signal and its variation with change in sodium flow rate are predicted by modeling and compared with experimental results.